2014
DOI: 10.1021/la501265k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Accuracy of the Poisson–Boltzmann Cell Model for Salty Suspensions

Abstract: The cell model is a ubiquitous, fast, and relatively easily implemented model used to estimate the osmotic pressure of a colloidal dispersion. It has been shown to yield accurate approximations of the pressure in dispersions with a low salt content. It is generally accepted that it performs well when long-ranged interactions are involved and the structure of the dispersion is solidlike. The aim of the present work is to determine quantitatively the error committed by assuming the pressure computed with the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 51 publications
5
32
0
Order By: Relevance
“…According to a multi-colloid PB Brownian dynamics simulation study by Hallez et al [60], the identification of the suspension osmotic pressure Π with the microion osmotic pressure calculated using the PB cell model is quite accurate for κ res d 1, but not reliable for κ res d 5, with a larger error introduced for intermediate values of κ res d that is strongly depending on (l B /a)|Z bare |. Here, d = a φ −1/3 − 1 is roughly twice the average intercolloid distance.…”
Section: Osmotic Pressure Calculationmentioning
confidence: 99%
“…According to a multi-colloid PB Brownian dynamics simulation study by Hallez et al [60], the identification of the suspension osmotic pressure Π with the microion osmotic pressure calculated using the PB cell model is quite accurate for κ res d 1, but not reliable for κ res d 5, with a larger error introduced for intermediate values of κ res d that is strongly depending on (l B /a)|Z bare |. Here, d = a φ −1/3 − 1 is roughly twice the average intercolloid distance.…”
Section: Osmotic Pressure Calculationmentioning
confidence: 99%
“…The shape of the macroion dictates the appropriate geometry of the cell (planar, cylindrical, spherical), the symmetry of which eases the computational solution of the nonlinear PB equation. Predictions for microion densities and osmotic pressure prove to be most accurate for systems with relatively low salt concentration [9,26].…”
Section: Introductionmentioning
confidence: 99%
“…for the cell model and 28) for the renormalized jellium model. The above boundary conditions, although necessary to solve the cell model and the renormalized jellium model do not prejudge (define) either the nature of the colloidal charge or the response of the latter to colloid density or to a change in the nature and concentration of the electrolyte solution.…”
Section: General Conditionsmentioning
confidence: 99%
“…This should not come as a surprise since the PCM is known to neglect the entropic and contact contributions to the osmotic pressure 28,58 . As discussed by Hallez et al 28 , it is found Figure 9.…”
Section: Osmotic Pressurementioning
confidence: 99%
See 1 more Smart Citation